Occupational injuries and contributing factors among industry park construction workers in Northwest Ethiopia - Tewodros Yosef; Enawgaw Sineshaw; Nigusie Shifera (Frontiers Media S.A., 2023)
BackgroundConstruction business is currently the second greatest source of injuries in Ethiopia after automotive accidents, with a risk of fatality that is five times higher than that of other industrial sectors. To establish measures for injury prevention, it is crucial to assess the severity of occupational injuries and identify the variables that contribute to them. Therefore, this study aimed to assess the magnitude and factors associated with occupational injuries among Bure Industrial Park construction workers, Northwest Ethiopia.MethodsAn institutional-based cross-sectional study was conducted among 372 construction workers at Bure Industrial Park. The study participants were selected using a simple random sampling method. The data were collected using interviewer-administered structured questionnaire and work environment observation using structured checklist. In the descriptive statistic, frequencies, proportion, and mean were calculated and the results of the analysis were presented in text and tables. The bi-variable and multivariable logistic regression analyses were carried out to identify independent factors having associations with the occurrence of occupational injury.ResultsThe overall prevalence of occupational injuries among Bure industrial park construction workers was 39.4%, 95%C.I (34.4%-44.4%). Factors such as sex (being male) [AOR = 1.74, 95%CI (1.02-2.97)], being married [AOR = 2.79, 95%CI (1.50-5.17)], no use of personal protective equipment [AOR = 1.67, 95%CI (1.12-2.85)], no training on occupational safety [AOR = 1.45, 95%CI (1.06-2.98)], and not satisfied with the job [AOR = 5.97, 95%CI (3.48-10.2)] were the factors associated with occupational injuries.Conclusion and recommendationThe finding shows the public health importance of occupational injury among construction workers in the study area. Numerous factors have been linked to workplace injuries, including sex, marital status, the usage of personal protection equipment, training in occupational safety, and job satisfaction. As a result, in order to lower the rate of occupational injury, employers should prioritize offering safety training, encouraging the use of personal protective equipment while working, conducting routine workplace inspections, and ensuring that their staff members are happy at work by providing comfortable workspaces.